Clinical and nutritional status in the late postoperative of pancreaticoduodenectomy: influence of pylorus preservation procedure - Muniz,Cinara Knychala (2012)
PURPOSE: To evaluate the nutritional status of patients in the late postoperative period of pancreaticoduodenectomy (PD) and compare the long-term outcome according to pylorus-preserving (PPPD) or the standard technique (SPD) in which the pylorus is resected. METHODS: This prospective study was conducted twelve months prior or more in patients who had underwent PD (PD Group, n=15) and health volunteers (Control Group, n=15). At a post hoc analysis, the PD Group was divided in PPPD Subgroup (n=9) and SPD Subgroup (n=6), according to the PD techniques. Gastrointestinal complaints and nutritional status were evaluated, apart from a biochemical assessment; Student t-test or Mann-Whitney test were used. RESULTS: The patients recovered their body weight and the gastrointestinal complaints were uncommon. The PD Group showed higher energy and protein intake even though BMI was lower than in Control Group. There were no differences in laboratorial data, except for higher glycemia, serum alkaline phosfatase and C-reactive protein in PD Group. There was no difference in the various parameters evaluated when the Subgroups (PPPD and SPD) were compared. CONCLUSION: For long-term pancreaticoduodenectomy, the gastrointestinal symptoms are minimal and the patients had the clinical and nutritional status preserved, regardless of pylorus preservation.